The influence of school climate and achievement on bullying: Comparative evidence from international large-scale assessment data. Issue 1 (2nd January 2022) - Bokhove, Christian; Muijs, Daniel; Downey, Christopher
ABSTRACT: Background: Bullying is widely acknowledged as one of the most harmful events in a child's life, leading to negative life experiences and outcomes. However, 'school effects of bullying' are rarely studied from an international perspective, especially with international large-scale data. Purpose: In this study, we aim to look at bullying through an international comparative approach, focusing on the contribution of the school, the education system and culture, and pupil level factors such as socio-economic status (SES) and gender. Our key question is whether school factors can affect bullying prevalence. Methods: We used data from six countries (USA, Finland, England, Romania, Korea and Italy) from the Trends in International Mathematics and Science Study (TIMSS), a large-scale international study. We used multilevel modelling to analyse the dataset. Findings: We find little evidence of a relation between country policies and levels of bullying, though there are differences in the extent to which school and pupil factors are related to bullying. The most consistent relationship was between gender and bullying, with prevalence higher among boys, while school factors were not significant. Conclusion: The findings indicate that 'one size fits all' school policies might not be the best course of action, and individual support might be a more fruitful avenue.